EMPLOYEE PRODUCTIVITY IN TERMS OF ENVIRONMENT, MOTIVATION, AND WORK DICIPLINE OF UD PRIMA JAYA SURAKARTA - Silviana Fransiska Anggreini; Sarsono Sarsono; Fithri Setya Marwati (JURNAL ILMIAH EDUNOMIKA, 2022)
Companies in carrying out their activities must have goals to be achieved. In realizing this goal, every company must have a precise strategy. One of the strategic targets in achieving goals is human resources. This is important because human resources are the key of a company to success reach. The purpose of study is to sees the effect of environment, discipline , and motivation, and on the productivity of UD Prima Jaya Surakarta employees. Descriptive quantitative is used in study. Primary data and secondary data are used in this study. The sampling technique used is the non-probability sampling technique with the saturated sample method. The results of this study from SPSS software is known if the environment, discipline, and motivation, have a positive effect on the productivity of UD Prima Jaya Surakarta employees. Keywords: Work Productivity, Environment, Discipline , and Motivation.